2016
DOI: 10.3354/dao03009
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of salmonid alphavirus (SAV) and piscine orthoreovirus (PRV) infections in wild sea trout Salmo trutta in Norway

Abstract: Viral diseases represent a serious problem in Atlantic salmon (Salmo salar L.) farming in Norway. Pancreas disease (PD) caused by salmonid alphavirus (SAV) and heart and skeletal muscle inflammation (HSMI) caused by piscine orthoreovirus (PRV) are among the most frequently diagnosed viral diseases in recent years. The possible spread of viruses from salmon farms to wild fish is a major public concern. Sea trout S. trutta collected from the major farming areas along the Norwegian coast are likely to have been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
5
11
0
Order By: Relevance
“…The probability of wild salmon being exposed to SAV from farms escapees was therefore low both when leaving the coast as smolts (2010–2011) and when returning as adults in 2012. The absence of SAV in the salmon tested is also consistent with previous findings that SAV infections are uncommon in wild salmonids irrespective of farming intensity or the frequency of PD outbreaks at the locations examined (Biering et al., ; Garseth et al., ; Madhun et al., ; Plarre & Nylund, ).…”
Section: Resultssupporting
confidence: 89%
“…The probability of wild salmon being exposed to SAV from farms escapees was therefore low both when leaving the coast as smolts (2010–2011) and when returning as adults in 2012. The absence of SAV in the salmon tested is also consistent with previous findings that SAV infections are uncommon in wild salmonids irrespective of farming intensity or the frequency of PD outbreaks at the locations examined (Biering et al., ; Garseth et al., ; Madhun et al., ; Plarre & Nylund, ).…”
Section: Resultssupporting
confidence: 89%
“…In the second study, sampling of brown trout took place in hatcheries: Given that the virus is present in a nonanadromous brown trout reservoir, it is more likely to be found in a hatchery where fish are kept together in tanks where transmission of pathogens between individuals is facilitated. The overall prevalence of PCR‐positive nonanadromous brown trout in this study was at par with previous studies in wild sea trout (Biering et al., ; Garseth, Fritsvold et al., ; Madhun et al., ). In previous studies, the viral loads (judged by C t values) have been low in all but one PRV‐positive trout.…”
Section: Discussionsupporting
confidence: 83%
“…None of the PRV‐3 positive seatrout selected for PRV‐1 analyses were PCR‐positive. Previous studies have shown that approximately 1%–3% of seatrout are PRV‐1‐positive (Garseth, Fritsvold, Opheim, Skjerve, & Biering, ; Madhun et al, ), but only one case had viral loads sufficiently high to enable sequencing and phylogenetic analyses. In that case, the sequence grouped together with PRV‐1 from wild and farmed salmon (Garseth et al, ).…”
Section: Discussionmentioning
confidence: 99%